Sandwich-like NiOx/NiCo2O4/Co3O4 nanoflakes enable efficient oxygen evolution electrocatalysis. (1st November 2019) - Chen, Jianyue; Ling, Yunhan; Lu, Zhaoxia; Huai, Xiaochen; Qin, Fei; Zhang, Zhengjun
Abstract: Water splitting is one of the most viable methods for obtaining green energy. However, due to the high energy consumption and low conversion efficiency of water splitting, it remains a challenge to design an oxygen-efficient and stable catalyst. In this work, NiOx nanoflakes were prepared by electrochemical co-deposition and dealloying, and Co3 O4 films were deposited on the NiOx nanoflakes by atomic layer deposition (ALD). After annealing, it was found by HRTEM that NiCo2 O4 formed between the NiOx nanoflakes and Co3 O4 layers. These nanoflakes had a low overpotential of 315 mV at a current density of 10 mA/cm 2 in a 1 M NaOH solution. Furthermore, the sandwich-like nanostructure also provided good oxygen evolution stability and a large carrier concentration. Due to the Co +2 /Co +3 and Ni +2 /Ni +3 electron pairs of NiCo2 O4 combined with NiOx and Co3 O4, the charge transferred easily and the activity increased. Thus, an efficient and simple OER catalyst was developed, which can contribute to the production of green energy. Graphical abstract: Image 1 Highlights: NiOx nanoflakes were successfully synthesized by de-alloying of NiW alloy in an alkaline environment. NiCo2 O4 was formed on NiOx nanoflakes by atomic layer deposition of Co3 O4 and then annealing. The new NiOx/NiCo2 O4 /Co3 O4 nanoflakes demonstrate superior electrocatalytic activity and stability.